Child oral health from the professional perspective – a global ICF‐CY survey. Issue 4 (15th September 2015) - Faulks, Denise; Molina, Gustavo; Eschevins, Caroline; Dougall, Alison
Abstract : Background: The International Classification of Functioning, Disability and Health Children and Youth version (ICF‐CY) (WHO) may serve as a tool for the application of holistic models of oral health. Aim: The ICF‐CY Global Oral Health Survey explored international professional opinion regarding factors relating to child oral health, including social environment, functioning, activity, and participation. Methods: Networking resulted in 514 professionals from 81 countries registering for a two‐round Delphi survey online. Participants were pooled into 18 groups according to six WHO world regions and three professional groups. In a randomized stratification process, eight from each pool ( n = 144) completed the survey. The first round consisted of eight open‐ended questions. Open‐expression replies were analysed for meaningful concepts and linked using established rules to the ICF‐CY. In the second round, items were rated for their relevance to oral health (86% response rate). Results: A total of 86 ICF‐CY items and 31 other factors were considered relevant to child oral health and function by at least 80% of professionals. Conclusions: The ICF‐CY can describe the holistic experience of oral health in children from the professional perspective. The data from this study will contribute to the development of an ICF‐CY Core Set in Oral Health.